Cobaltita de bário (Ba2Co9O14): caracterização estrutural e performance eletroquímica para reação de evolução de oxigênio e cerâmicas protônicas - Lapenda Filho, Antonio Carlos (2023)
Energy generation can be better utilized when energy efficiency and lower environmental risk are combined, especially in areas where the use of petroleum derivatives is present. Studies in the area of electrochemistry help in the development of devices such as low-cost, high-performance catalysts, which are essential for electrochemical applications, such as “water splitting” (WS) and fuel cells. In this work, the plate-type compound Ba2Co9O14 (BCO) was synthesized using the solid state reaction method and its potential as an electrocatalyst for the oxygen evolution reaction (OER) and as an electrode for proton ceramic cells was evaluated. (PCC). Regarding OER, the BCO obtained exhibited an overpotential of 366 mV at 10 mA/cm² and a Tafel slope of 67 mV/dec, a result superior to those reported for most materials based on cobaltite. The parameters of double layer capacitance (Cdl), electrochemically active surface area (ECSA) and specific activity (SA), which reflect the performance of the BCO, were determined to be 4.98 mF/cm²; 124.5 cm² and 3.58 mA/cm², respectively. Regarding proton-conducting ceramics, BCO is used for the first time as an electrocatalyst for oxygen reactions in PCCs in contact with an electrolyte BaZr0.852Y0.148O3-δ (BZY15) + 4 mols% ZnO (as sintering agent ). The BCO exhibits electrochemical performance comparable to current state-of-the-art oxygen electrode under humid conditions (PH2O ~ 10-2 atm), and also demonstrates excellent chemical compatibility with the BZY15 electrolyte. Due to the plate-like morphology of the BCO electrode grain and considering its weak bulk ionic conduction, the surface diffusion process becomes highly important in explaining the high-performance electrochemical behavior, in addition, the analysis of impedance spectroscopy data shows electronic leakage within the electrolytic substrate, but to solve this problem a data correction is applied, revealing that the electrode kinetics are strongly limited by the diffusion of oxygen on the surface of the BCO grains towards the triple phase boundary, where the proton transfer, releasing water. In contrast, the oxygen adsorption and/or dissociation steps are facilitated given the predominantly electronic character of the BCO material, which is suggested to originate from a small polaron jump between the Co3+/Co2+ pairs.